Upaya Meningkatkan Disiplin Guru Dalam Kehadiran Mengajar di Kelas Melalui Penerapan Reward Dan Punishment di SMP N 2 Kampar Kiri Hilir - Jamaluddin, Jamaluddin (Komunitas Manajemen Kompetitif, 2017)
Schools that are away from the crowds make a lot of trouble, including lack of enthusiasm teachers present every day to school. The absence of teachers coming to school makes the school learning atmosphere uncertain and even student learning outcomes become very problematic. There is a need to motivate teachers such as by applying rewards and punishment to teachers. Through school action research methods applied in schools with three cycles and research results show that discipline in teaching attendance increases with the application of reward and punishment methods. Keywords: Teacher discipline, reward and punishment methods